Effects of shiga toxin 2 on cellular regeneration mechanisms in primary and three-dimensional cultures of human renal tubular epithelial cells. (October 2016) - Márquez, Laura B.; Araoz, Alicia; Repetto, Horacio A.; Ibarra, Fernando R.; Silberstein, Claudia
Abstract: Shiga toxin (Stx)-producing Escherichia coli (STEC) causes post-diarrheal Hemolytic Uremic Syndrome (HUS), which is one of the most common causes of acute renal failure in children in Argentine. The aim of the present work was to study the effects of Shiga toxin type 2 (Stx2) on regenerative mechanisms of primary cultures of human cortical renal tubular epithelial cells (HRTEC) and three-dimensional (3D) cultures of HRTEC. Primary cultures of HRTEC were able to develop tubular structures when grown in matrigel, which showed epithelial cells surrounding a central lumen resembling the original renal tubules. Exposure to Stx2 inhibited tubulogenesis in 3D-HRTEC cultures. Moreover, a significant increase in apoptosis, and decrease in cell proliferation was observed in tubular structures of 3D-HRTEC exposed to Stx2. A significant reduction in cell migration and vimentin expression levels was observed in HRTEC primary cultures exposed to Stx2, demonstrating that the holotoxin affected HRTEC dedifferentiation. Furthermore, a decreased number of cells expressing CD133 progenitor marker was found in HRTEC cultures treated with Stx2. The CD133 positive cells also expressed the Stx receptor globotriaosylceramide, which may explain their sensitivity to Stx2. In conclusion, Stx2 affects the regenerative processes of human renal tubular epithelial cells in vitro, by inhibiting cell dedifferentiation mechanisms, as well as tubules restoration. The development of 3D-HRTEC cultures that resemble original human renal proximal tubules is a novel in vitro model to study renal epithelial repair mechanisms after injury. Highlights: Renal epithelial cells are able to develop 3D-tubular structures. Shiga toxin 2 inhibited tubulogenesis in 3D-human renal cultures. Shiga toxin inhibited dedifferentiation in human renal tubular epithelial cells. CD133 + human renal tubular cells are sensitive to shiga toxin 2.